Trust in the police and crime reporting: Reassessing assumptions in the context of violent crime in England and Wales - Timukaite, Aiste (International review of victimology, 2025)
The reporting of crime to the police is crucial for an efficient functioning of the criminal justice system. It is widely argued that victims’ decision to contact the police is based on considerations of the anticipated costs and benefits of crime reporting. Scholars have previously suggested that victims’ attitudes towards the police may influence their perceptions of the costs and benefits associated with crime reporting. However, victims’ trust in the police as a multidimensional construct has not been empirically tested as a predictor of victims’ crime reporting to the police. This study uses Crime Survey for England and Wales data from 2017/2018 to 2019/2020 to explore the relationship between victims’ trust in police effectiveness and violent crime reporting behaviour. Furthermore, this study examines the influence of victim and situational characteristics on decisions to report victimisation to the police. Our analysis reveals that victims’ trust in police effectiveness does not predict their decision to disclose violent crime victimisation to the police. However, victims’ sex and age significantly influence reporting decisions. Moreover, our findings reveal that situational factors, specifically the presence of a weapon and injury to the victim, are important predictors of violent crime reporting.